Pengembangan Buku Cerita Bergambar untuk Meningkatkan Minat Belajar Siswa Kelas II MI Kebokicak Dapurkejambon Jombang - Fadhilah, Farah Diva Nailal (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
Abstract: Learning the subject of faith and morals at MI Kebokicak Dapurkejambon Jombang tends to be boring. So far, teachers of faith and morals have mostly used the lecture method. Whereas students need supporting media that can help them to understand the lessons of faith and morals. Researchers developed picture storybook learning media as an effort to increase student interest in learning. Therefore, it is necessary to develop media that supports the process of learning faith and morals to achieve learning objectives. This study uses the Research and Development method or called (R&D) by following the steps developed by Borg & Gall. Starting from the preparation and data collection stage, the development stage, the product trial stage, the revision stage, the field trial stage, finally the dissimilation and implementation stage. The instruments in this study were interviews, observations and questionnaires. This research was conducted at MI Kebokicak Dapurkejambon Jombng. The results of this study indicate that 1. The application of picture story book learning media in the subject of aqidah akhlaq class II at MI Kebokicak Dapurkejambon Jombang 2. The application of the development of picture story book learning media through the Borg & Gall development model through several development procedures. Students are very enthusiastic about using picture story book media products. It is hoped that students will be able to understand the material because of its attractive appearance. 3. The form of increasing student learning interest through test results with an average value of 76% before using picture story book learning media, while an average value of 88% was obtained after using picture story book learning media. validation from material experts and design experts with the results of the validity test from the development of learning media meets the valid criteria with the results of the material validation test reaching 90% and the results of the design expert validation reaching 88%.